Environmental Refugees: Study of the Legal Policies of ASEAN Countries on the Phenomenon of Refugees due to Climate Change - Cholidah Cholidah; Fitria Esfandiari (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
This research is conducted by using normative juridical method that will analyse the concept of refugees in the Convention of Geneva 1959 which is examined by the framework of protection against movement of people including due to climate change factor in A/RES 73/195 which is the adoption of the Global Compact for safe, orderly and regular migration as well as protection against refugees due to climate change 1951 in the Ratify it. The author argues that, the refugee problem caused by global climate change is not a future discourse that is far from reality, this problem becomes a necessity along with the development effort, especially the development of Not consider the concept of sustainability of the world ecosystem. So the minimum protection must be done either by the state Convention ratification 1951 nor the state Non ratification of this Convention on the Protection of refugees In General that is listed In standard This convention should be provided also against Environmental Refugees on the basis that the term refugee contained in this term should include against refugees due to the unlikely climate change returning to its home country due to an environment that has not supported life Refugees.Keywords: ASEAN; Policies; Climate Change; Environmental refugees AbstrakPenelitian ini dilakukan dengan menggunakan metode yuridis normatif yang akan menganalisis konsep pengungsi dalam Konvensi Jenewa 1959 yang dikaji dalam kerangka perlindungan terhadap pergerakan orang termasuk akibat faktor perubahan iklim dalam A/RES 73/195 yang merupakan adopsi Global Compact untuk migrasi yang aman, tertib dan teratur serta perlindungan terhadap pengungsi akibat perubahan iklim 1951 di Ratifikasi itu. Penulis berpendapat bahwa, masalah pengungsi akibat perubahan iklim global bukanlah wacana masa depan yang jauh dari kenyataan, masalah ini menjadi keniscayaan seiring dengan upaya pembangunan, terutama pengembangan konsep keberlanjutan ekosistem dunia. Jadi perlindungan minimal harus dilakukan baik oleh negara ratifikasi Konvensi 1951 maupun negara Non ratifikasi Konvensi ini tentang Perlindungan Pengungsi Secara Umum yang tercantum Dalam standar Konvensi ini harus diberikan juga terhadap Pengungsi Lingkungan atas dasar bahwa istilah pengungsi yang termuat dalam istilah ini harus mencakup terhadap pengungsi akibat perubahan iklim yang tidak mungkin kembali ke negara asalnya karena lingkungan yang belum mendukung kehidupan Pengungsi.Kata Kunci: ASEAN; Kebijakan; Perubahan iklim; Pengungsi lingkungan